Active Noise-Vibration Control using the Filtered-Reference LMS Algorithm with Compensation of Vibrating Plate Temperature Variation - MAZUR, Krzysztof; PAWEŁCZYK, Marek (Archives of Acoustics, 2011)
Vibrating plates have been recently used for a number of active noise controlapplications. They are resistant to difficult environmental conditions including dust,humidity, and even precipitation. However, their properties significantly dependon temperature. The plate temperature changes, caused by ambient temperaturechanges or plate heating due to internal friction, result in varying response of theplate, and may make it significantly different than response of a fixed model. Suchmismatch may deteriorate performance of an active noise control system or evenlead to divergence of a model-based adaptation algorithm.In this paper effects of vibrating plate temperature variation on a feedforwardadaptive active noise reduction system with the multichannel Filtered-reference LMSalgorithm are examined. For that purpose, a thin aluminum plate is excited withmultiple Macro-Fiber Composite actuators. The plate temperature is forced by a setof Peltier cells, what allows for both cooling and heating the plate. The noise isgenerated at one side of the plate, and a major part of it is transmitted through theplate. The goal of the control system is to reduce sound pressure level at a specifiedarea on the other side of the plate.To guarantee successful operation of the control system in face of plate temperaturevariation, a gain-scheduling scheme is proposed to support the FilteredreferenceLMS algorithm.